استخدام تقنية التسويق الفيروسي كآلية للترويج (مجلة الواحات للبحوث والدراسات, 2020)
The Purpose Of This Study Was To Understand The Role And The Importance Of Viral Marketing In The Promotion Process. Erea Of Marketing. Thus, And Due The Modernity Of This Topic Theoretically And Practically, This Study Came To Reflect The Importance Of The Role It Plays In Promotion And How Its Different Tools And Strategies Can Be Utilized In Order To Conveying The Advertising Message. Viral Marketing Relies On Using Technology With All Its Available Means And With The Least Costs Through Making Customers The Center Or The Mediator Of This Process. This Is The Core Of This Study Since Its Variables Are Using Viral Marketing Tools And Promotion, Especially Using Viral Marketing As A Means Of Promotion. Through An Analytical Study Of The Literature Of The Subject, This Study Reached A Set Of Results, The Most Important Of Which Is That The Use Of Viral Marketing Has An Effective Role In Enhancing The Promotional Process Of Enterprises By Making The Customer Act As The Main Mediator Instead Of Them, Which Reduces Costs And Increase The Effective Power Of Promotional Messages.  Accordingly, The Most Important Recommendation Was That The Enterprises Should Increase The Involvement Of Viral Marketing In Their Marketing Plans By Employing Its Tools And Strategies And Relying On Them To Transmit And Deliver Their Promotional Messages To Their Target Markets. Key Words- Viral Marketing, Customers, Promotional Messages,   Promotion, Mediator.